Nutritional Knowledge and Ergogenic Aid Using Status of Competitive and Recreational Cyclists - Erkan Günay; Dilara Sak; Taygun Dayı; Adile Öniz (Pamukkale University, 2022)
This study aimed to determine cyclists' nutritional knowledge and habits, and nutritional ergogenic aid usage and shed light on the relation between cyclists' nutritional knowledge and ergogenic aid usage. It was conducted in Cyprus. There were three groups (study groups: competitive cyclists-CC, recreational cyclists-RC; control group-CG: sedentary adults). Data were collected with a questionnaire that had three sections (the first two sections were related to general nutritional habits, ergogenic aids, anthropometric measurements, and the last section included The Nutrition for Sport Knowledge Questionnaire-NSKQ). All data were evaluated by Statistical Package for the Social Science-SPSS version 24.0. Totally 174 adults participated voluntarily in this study (n: 58 for each group). CC and RC skipped their main meals and smoked less than CG (p